Literasi Produk Bersertifikasi Halal Dalam Rangka Meningkatkan Penjualan Pada UMKM - Siti Indah Purwaning Yuwana; Hikmatul Hasanah (Jurnal Pengabdian Masyarakat Madani, 2021)
Many local products produced by SMEs in Jember circulating without halal labeling makes the authors compelled to do community service about literacy of halal certification products. Some MSME actors have made changes by managing the halal certification process for their products, so as to increase public confidence in making purchases, which has an impact on increasing product sales turnover. However, the number of business actors who carry out the certification is not comparable to the number of products produced by MSMEs circulating without halal certification. This paper describes the literacy assistance program carried out by the author in its function to provide understanding and knowledge related to halal certification in several MSMEs in Sumbersari District, Jember Regency. Our service program through literacy workshops carried out in two sessions, namely the first session providing theoretical exposure about the meaning of halal products and halal certification, then the next session providing stages of the process of obtaining halal product certification and examples of MSME actors who have implemented it. The results of this community service program have a positive impact on MSME actors, namely understanding the importance of obtaining halal certification and its effect on sales volume. In addition, MSME actors also understand how the stages of managing halal product certification are.